ANALISIS VARIASI VEKTOR KECEPATAN GPS PULAU JAWA TAHUN 2011 - 2018 MENGGUNAKAN METODE PRINCIPAL COMPONENT ANALYSIS (PCA) - Lulu Tiaratama, Agidia
Java is one of the quite large islands of very active tectonic activity which is located north of the Java subduction zone in the form of a meeting zone of the Indo-Australian Plate with the Sunda Plate. The movement of faults on the island of Java (Dengkeng Fault, Opak Fault) has been investigated from the eastern fault of Java Island (Kuncoro et al., 2018), in Yogyakarta from faults caused by the subduction of the Australian Plate under the Eurasian Plate (Abidin et al., 2009), as well as the Lembang fault and other faults along Java. Research on the analysis of velocity vector variations as a description of deformation is carried out through continuous processing of GPS (Global Positioning System) observations from BIG’s (Geospatial Information Agency) CORS (Continuously Operating Reference Station) in the southern part of Java Island. With daily processed coordinate data, the PCA (Principal Component Analysis) method which is one of the standard mathematical methods that transforms a number of different variables, but correlates to a small number of uncorrelated variables is called the principal component (PC) (Amiri-Simkooei et al., 2011) applied to separate tectonic signals in the form of global time series data and non-tectonic data in the form of local time series data by applying the rules for selecting dominant variants of eigen values for PC formation and orthogonal eigen vectors as weights in minimizing correlations. The results from global and local time series data are used to calculate the magnitude of the shift velocity from 2011 until 2018. The processing results show the resultant velocity vector in the initial data intermittent 0.0610 to 10.4616 mm/year, global data from 0.0647 to 10.3967 mm/year, and local data of 0.0037 to 1.9985 mm/year. The spatial variation of the GPS observations velocity data of the PCA domain data horizontally moves northeast to the south west region of Java and East Java; and move to the southeast in the south central region of Java from West Java to DIY. Variations for increase and decrease vary throughout the southern regions of Java.